2012
DOI: 10.4236/aim.2012.24064
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of <i>Gallibacterium anatis</i> to Chicken Oropharyngeal Epithelial Cells and the Identification of Putative Fimbriae

Abstract: Microbial infections are typically initiated by the colonization of tissues by a specific mechanism that promotes adherence to host cells or tissues. In this work, we characterized the ability of Gallibacterium anatis F149 T to express fimbriae that may be involved in mucosal attachment. Using transmission electron microscopy, the fimbriae-like structures could be observed on the surface of negatively stained G. anatis F149 T , and these structures were further visualized after being released by physical shaki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Few virulence factors have been described to be expressed by this bacterium: chicken IgG-degrading secreted proteases (García-Gómez et al, 2005), expression of a RTX (Repeat in toxin) protein (Kristensen et al, 2010), as well as the ability to agglutinate red blood cells (Zepeda et al, 2009;Montes-García et al, 2016), and the ability to adhere to plastic surfaces and to form biofilms on glass (Vaca et al, 2011;Persson and Bojesen, 2015). This last capability could be supported by the fimbriae expression described recently (Salgado-Lucio et al, 2012;Bager et al, 2013;Kudirkiene et al, 2014;López-Ochoa et al, 2017) or by the participation of other molecules as putative adhesins like the EF-Tu protein (López-Ochoa et al, 2017). However, the response to different stresses and the putative relationship with virulence factors expression have not been studied.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Few virulence factors have been described to be expressed by this bacterium: chicken IgG-degrading secreted proteases (García-Gómez et al, 2005), expression of a RTX (Repeat in toxin) protein (Kristensen et al, 2010), as well as the ability to agglutinate red blood cells (Zepeda et al, 2009;Montes-García et al, 2016), and the ability to adhere to plastic surfaces and to form biofilms on glass (Vaca et al, 2011;Persson and Bojesen, 2015). This last capability could be supported by the fimbriae expression described recently (Salgado-Lucio et al, 2012;Bager et al, 2013;Kudirkiene et al, 2014;López-Ochoa et al, 2017) or by the participation of other molecules as putative adhesins like the EF-Tu protein (López-Ochoa et al, 2017). However, the response to different stresses and the putative relationship with virulence factors expression have not been studied.…”
Section: Introductionmentioning
confidence: 85%
“…To evaluate the immunogenicity of stressed and unstressed cultures of G. anatis , extracted proteins were separated by 10% SDS-PAGE and transferred to a nitrocellulose membrane, as described previously, to determine proteins over- or under-expressed in the iron-restricted medium ( Abascal et al, 2009 ). In this assay, membranes were incubated under one of the three following conditions: with a 1:1,000 diluted polyclonal serum pooled from chickens experimentally infected with G. anatis ( Salgado-Lucio et al, 2012 ), anti-transferrin binding proteins (TbpA and TbpB) from Avibacterium paragallinarum ( Abascal et al, 2009 ), or biotinylated-chicken hemoglobin. Next, the membranes were washed three times with phosphate-buffered saline-0.5% Tween 20.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As changes in bacterial aggregation have been observed through treatment with proteases and fibrillar structures by electron microscopy of G. anatis biofilms (Vaca et al, 2011;Salgado Lucio et al, 2012), we asked how some extracellular proteins of G. anatis are expressed, as they could form cellular junctions within the biofilms or bridges of cells with solid surfaces, so the abundances of the mRNA of the fimbrial Frontiers in Microbiology 07 frontiersin.org genes flf1_a, flf3_b, flf_b, flf1_D, flf3_D, and flf_D (Figure 2A) were determined at the transcriptional level (Figure 2B). Absolute quantitation of the transcripts by qRT-PCR was performed by using standard curves prepared for each of the genes; the expression of each transcript was different, and the flf3 gene primers did not amplify any fragment from ESV200 DNA, either due to variations in the target sequence of the primers or due to the absence of the gene in the genome of the ESV200 strain.…”
Section: Gallibacterium Anatis Esv200mentioning
confidence: 99%
“…Similar data have been reported by Wurpel et al (2016) , who found that fimbriae are involved in biofilm formation and adherence to human cells. Interesting data are obtained when comparing natural bacterial isolates; a majority of G. anatis strains produce filaments arranged as latices and form biofilms, exhibiting adhesion to cells and inert surfaces ( Vaca et al, 2011 ; Salgado Lucio et al, 2012 ), and it has been proposed that some G. anatis lineages carry different F17-like fimbriae and are more virulent ( Bager et al, 2013b ; Pors et al, 2016 ). The molecular classification of the F17-like genes into operons was performed by Kudirkiene et al (2014) .…”
Section: Introductionmentioning
confidence: 99%